Marine organisms entrapment at Sejingkat coal power plant, Kuching, Sarawak - Michael, Tingang Engan (Universiti Malaysia Sarawak (UNIMAS), 2014)
The main objectives of the study were to; (i) determine the density and diversity of marine organisms entrapped by Sejingkat Coal Fired Power Plant, Kuching, Sarawak; to document selected water quality parameters. The density and diversity of marine organisms were determined based on the number and its species being entrapped at the cooling water intake filters at Sejingkat Coal Power Plant (SPC) were collected on two to three hourly basis depending on the filters efficiency during pumping of cooling water.